2020
DOI: 10.1002/1873-3468.13933
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the role of sphingosine 1‐phosphate in cancer

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive lipid that binds to a family of G protein-coupled receptors (S1P 1-5) and intracellular targets, such as HDAC1/ 2, that are functional in normal and pathophysiologic cell biology. There is a significant role for sphingosine 1-phosphate in cancer underpinning the socalled hallmarks, such as transformation and replicative immortality. In this review, we survey the most recent developments concerning the role of sphingosine 1-phosphate receptors, sphingosine kinase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 134 publications
(155 reference statements)
0
44
0
Order By: Relevance
“…For example, many colon cancers exhibit overexpression of SphK1, and a SphK1 knockout mouse model that was exposed to azoxymethane developed less colon tumors than wild-type mice [36]. A similar effect was found in triple-negative breast cancer (TNBC), which has overexpressed S1P [37][38][39]. Exogenous SphK1 and SphK1 overexpression was also found to induce migration, proliferation, and invasion of ovarian cancer cells in vitro.…”
Section: Sphingosine Kinase 1 Andmentioning
confidence: 87%
“…For example, many colon cancers exhibit overexpression of SphK1, and a SphK1 knockout mouse model that was exposed to azoxymethane developed less colon tumors than wild-type mice [36]. A similar effect was found in triple-negative breast cancer (TNBC), which has overexpressed S1P [37][38][39]. Exogenous SphK1 and SphK1 overexpression was also found to induce migration, proliferation, and invasion of ovarian cancer cells in vitro.…”
Section: Sphingosine Kinase 1 Andmentioning
confidence: 87%
“…Sphingosine 1-phosphate (S1P) is generated by sphingosine kinases 1 and 2 (SphK1 and SphK2) and is a bioactive lipid mediator, which acts both as a second and a first messenger. It is able to bind to five G-protein coupled receptors S1P1R-5 and to regulate different aspects of cancer progression, including cell proliferation, apoptosis, migration, inflammation and angiogenesis [16,45]. Many studies have suggested that the SphK1/S1P axis could play a role in the promotion of several types of tumors, based on the overexpression of SphK1 in tumor cell lines and in patient samples, and sometimes, on the measured increased S1P levels in tumors and/or in patient blood.…”
Section: Sphingosine-1-phosphatementioning
confidence: 99%
“…SPHK2 has basal activity towards sphingosine; however, SPHK2 can be activated by a variety of factors and conditions, including epidermal growth factor (EGF) in cancer cells Pyne and Pyne (2020) and hypoxia in cerebral microvascular endothelial cells (Wacker et al, 2009). Human SPHK2 is phosphorylated at Ser351 FIGURE 1 | Metabolic pathway of sphingolipids.…”
Section: Regulation Of Sphk2mentioning
confidence: 99%
“…As described above, SPHK2 is involved in tumorigenesis of diverse types of cancers. Pharmacologically inhibiting SPHK2 is beneficial in prostate, breast, ovarian, pancreatic and kidney, colon, liver, blood, and lung cancers (Pyne and Pyne, 2020). Various SPHK2 inhibitors are being developed to treat cancer, including SPHK2-specific sphingosine-competitive small molecules (Magli et al, 2019).…”
Section: Sphk2 and Cancermentioning
confidence: 99%
See 1 more Smart Citation